Improving Mastery of Indonesian Vocabulary through Music Mnemonic Method and Picture Cards in Elementary School - wahdian, Agus; Kusyairi; M. Khoiri, M. Khoiri (Universitas Pendidikan Ganesha, 2023)
At this time, the subject of Indonesian is not a compulsory subject in schools. However, mastering Indonesian vocabulary still requires more work for many students. The complex information in the linguistic rules of the language subject in Curriculum 2013 makes it difficult for students to memorize. This study aims to improve grade 4 Indonesian vocabulary mastery in elementary school through music mnemonic and picture card methods. The research design used was a quasi-experimental study with a between-subject design. The between-subject design is an experimental research design involving two or more groups given different treatments. The design used in this study was a pre-test-post-test control group design. The participants were 30 students aged 9-11 with Indonesian vocabulary mastery scores below the average. The results showed an increase in Indonesian vocabulary mastery through music mnemonic and picture card methods for grade 4 students in elementary school. The group with music mnemonics has the highest score due to the multimodality of various memorization methods that impact the chunking effect on working Memory so that new information can more easily enter the Long-Term Memory. It is concluded that the use of accrostic-type mnemonic techniques has a significant effect on students’ memory level. This study provides input to teachers and schools to combine several methods in providing learning in accordance with children's cognitive development stage.